Design and construction of wideband VNA ground-based radar system with real and synthetic aperture measurement capabilities - Lim, K. -S.; Koo, V. -C. (EMW Publishing, 2008)
This paper presents the design and construction of an advanced wideband, automated radar system. With the aid of Vector Network Analyzer (VNA), a wideband ground-based system can be achieved with proper Radio Frequency (RF) circuitry integration. The RF circuitry is designed specifically to configure the proposed system to be able to measure full linear polarimetric scattering matrices of the area of interest. Besides, quasi-monostatic horn antenna configuration is chosen to transmit and receive the electromagnetic wave. The goal of this paper is to demonstrate the real and synthetic aperture capabilities of the system in outdoor measurement with the microwave frequency range from 2 to 7 GHz. Coupled with the integration of the Automatic Antenna Positioning System (AAPS), the constructed system is able to perform real and synthetic aperture radar measurements. A series of measurement was done on real aperture radar measurement using point target for validity purpose. The overall results show good agreement with the theoretical values. On the other hand, the proposed system is capable to performing a radar imaging measurement. A preliminary analysis is done on a 45 days old rice field. A three dimensional (3-D) radar image has also been constructed successfully with Range Migration Technique (RMA). The result shows good potential of the system in constructing radar imaging of natural target.